Direct stimulation of immediate-early genes by intranuclear insulin in trypsin-treated H35 hepatoma cells. - Lin, Y J (1992)
H35 hepatoma cells were treated with trypsin to abolish insulin binding and insulin-stimulated receptor kinase activity. Insulin was, however, internalized by fluid-phase endocytosis in trypsin-treated cells. Furthermore, nuclear accumulation of insulin was similar in control and trypsin-treated hepatoma cells. Northern blot analysis revealed insulin increased g33 and c-fos mRNA concentrations identically in control and trypsin-treated cells but had no effect on beta 2-microglobulin mRNA. Actinomycin D treatment prior to or after insulin addition demonstrated that insulin increased gene transcription and had no effect on mRNA degradation. These studies suggest that the accumulation of intact insulin in cell nuclei may be directly involved in the increased transcription of immediate-early genes.